Biodiversity and Community Structure of Mormyridae (Pisces: Teleostei: Osteoglossiformes) from Niger River in Northern Benin: Threats, Conservation and Valorization Perspectives - ADJIBADE, Nambil Kayodé; Adite, Alphonse; ARAME, Hamidou; SIDI IMOROU, Rachad; SONON, Pejanos Stansilas (My University, 2019)
Mormyrid fishes are of great commercial and economic importance in the artisanal fisheries of the Niger River in Benin. We investigated species composition and community structure of this taxa in order to contribute to species management and sustainable exploitation. Mormyrid individuals were collected monthly from February 2015 to July 2016 using cast nets, gill nets and seines. Among a total of 6825 individuals collected, eleven (11) species belonging to 9 genera were inventoried. Numerically, Marcusenius senegalensis dominated the fish assemblages and made 43.74% of the mormyrid sub-community followed by Mormyrus macrophthalmus (14.87%), Hyperopisus bebe, (11.43%), Petrocephalus bovei (11.21%), Mormyrus rume (8.54%) and Hippopotamyrus pssittacus (4.69%). The Shannon-Weaver index of species diversity was moderate and reached H‟=2.54. Overall, percentage occurrences (PO) of Mormyrids in the 5 selected sites ranged between 40 and 100%, with Marcusenius senegalensis (PO=100%) and Hyperopisus bebe (PO=100%) widely distributed in all 5 sites. In the Niger River, Mormyrid abundances significantly (r=0.70; P<0.01) increased with dissolved oxygen. The overexploitation and other antropogenic disturbances such as domestic uses (ditch cleanings, clothe washings, bathings), invasion of floating plants (Echhornia crassipes), sand dragging, human wastes dumping, the use of chemical fertilizers and pesticides for adjacent agriculture etc. constituted some major threats for the growth and survival of the Mormyrids in the Niger River. The results of this study will contribute to design a holistic species management scheme that includes habitat protection, species conservation and valorization.Mormyrid fishes are of great commercial and economic importance in the artisanal fisheries of the Niger River in Benin. We investigated species composition and community structure of this taxa in order to contribute to species management and sustainable exploitation. Mormyrid individuals were collected monthly from February 2015 to July 2016 using cast nets, gill nets and seines. Among a total of 6825 individuals collected, eleven (11) species belonging to 9 genera were inventoried. Numerically, Marcusenius senegalensis dominated the fish assemblages and made 43.74% of the mormyrid sub-community followed by Mormyrus macrophthalmus (14.87%), Hyperopisus bebe, (11.43%), Petrocephalus bovei (11.21%), Mormyrus rume (8.54%) and Hippopotamyrus pssittacus (4.69%). The Shannon-Weaver index of species diversity was moderate and reached H‟=2.54. Overall, percentage occurrences (PO) of Mormyrids in the 5 selected sites ranged between 40 and 100%, with Marcusenius senegalensis (PO=100%) and Hyperopisus bebe (PO=100%) widely distributed in all 5 sites. In the Niger River, Mormyrid abundances significantly (r=0.70; P<0.01) increased with dissolved oxygen. The overexploitation and other antropogenic disturbances such as domestic uses (ditch cleanings, clothe washings, bathings), invasion of floating plants (Echhornia crassipes), sand dragging, human wastes dumping, the use of chemical fertilizers and pesticides for adjacent agriculture etc. constituted some major threats for the growth and survival of the Mormyrids in the Niger River. The results of this study will contribute to design a holistic species management scheme that includes habitat protection, species conservation and valorization.
Keywords: Benin; Community Structure; Conservation; Management; Mormyrids; Niger River; Shannon-Weaver Index